Method for preparing thiol-functionalized cellulose nanocrystals for applications in rubber

By combining thiol esterified functionalized cellulose nanocrystals (CNCs) with rubber, using esterification and thiol-ene "click" crosslinking technology, the problems of poor dispersion and poor compatibility in rubber are solved, and the mechanical properties of the rubber are significantly improved.

CN120187762APending Publication Date: 2025-06-20MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051086.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-30
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

In the prior art, cellulose nanocrystals (CNCs) in rubber have poor dispersion and poor interfacial properties due to the poor compatibility between polar surfaces and non-polar SBR matrix, which limits their application in rubber.

Method used

The thiol esterified functionalized cellulose nanocrystals (CNCs) were prepared by step-by-step method, and the esterification and thiol-ene "click" crosslinking technology were used to introduce thiol ester and disulfide functional groups to improve the compatibility of CNC with rubber.

Benefits of technology

The good dispersion and compatibility of CNC in rubber is achieved, and the mechanical properties of rubber are improved, especially in terms of strain and true separating modulus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120187762A_ABST
    Figure CN120187762A_ABST
Patent Text Reader

Abstract

The present invention relates to improved cellulose nanocrystal fillers for rubber compositions, and more particularly to the grafting of disulfides and thioesters onto cellulose nanocrystals to improve performance as fillers in rubber compositions. At least one embodiment describes a method of grafting a thiol or disulfide on a CNC surface by, for example, esterification of 3-mercapto-propionic acid (MPA), 3-(acetylthio) propionic acid (APA), or dithiodipropionic acid (DTDPA). The reaction can be carried out on CNC that is highly dispersed in a suitable solvent and the reaction conditions are improved to achieve an advantageous degree of substitution DS. Embodiments further disclose how the surface thiol groups may then be protected in a second step as thio esters or asymmetric disulfides to modulate the hydrophobicity of CNC to improve compatibility with styrene-butadiene, SBR or natural rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The subject matter of the present invention relates to reinforcing fillers for rubber and, in particular, to the surface grafting of disulfides and thioesters onto cellulose nanocrystals for use in rubber compositions. Background Art

[0002] Commercial rubber products contain significant amounts of fillers and additives to modulate the viscoelastic properties of the cured product for optimal performance and lifespan. The development towards more sustainable components for rubber products provides an opportunity for bio-derived chemicals and materials, including cellulose nanocrystals (one or more “CNCs”). Due to their large specific surface area, particle geometry, and reactive surface, CNCs can be used as high-performance reinforcing agents for styrene-butadiene rubber (“SBR”) products. However, CNCs with polar surfaces have poor dispersibility and interfacial properties with non-polar SBR matrices by selectively and controllably generating CNC-elastomer covalent bonding interactions during rubber mixing.

[0003] Functionalized CNCs have been developed as reinforcing fillers for forming covalent crosslinks with UV-cured or vulcanized rubber elastomers, where varying degrees of reinforcement have been reported in natural rubber, NR, and SBR elastomers. Despite the successful modification of nanocellulose in these cases, all these reports describe marginal improvements in mechanical properties, which are essentially attributed to the poor compatibility between the functionalized filler and non-polar SBR. Functionalized CNCs with excellent dispersibility and compatibility in the resulting elastomer mixture would be useful. Such functionalized CNCs can also be used as reinforcing fillers in UV-cured or vulcanized rubber elastomers. Summary of the Invention

[0004] Aspects and advantages of the present invention will be set forth in part in the following description, or may be obvious from the detailed description, or may be learned by practice of the present invention.

[0005] This disclosure relates to cellulose nanocrystal reinforced fillers. Specifically, thiol-esterified functionalized cellulose nanocrystal reinforced fillers and methods for their preparation are provided. One embodiment of the invention is disclosed herein, wherein a stepwise method is used in the preparation of the functionalized CNC. The first step aims at high-yield esterification (e.g., grafting with methacrylic anhydride), followed by thiol-ene "click" crosslinking. The invention also teaches that alkene hydrothiolation chemistry generates grafted functional groups introduced by monosulfide linkages, which results in the reaction of thioacids with alkenes to produce thioesters. Thioacetic acid and thiobenzoic acid (both commercially available thioacids) are selected to compare the reactivity towards acyl click reactions and the compatibility of the isolated click products. In addition, thiol-ene click chemistry can also be used to graft branched thiols onto alkene-modified CNCs. Pentaerythritol tetra(3-mercaptopropionate) (PETMP), a commercially available four-arm thiol, can be used as a crosslinking agent for branched polyvinyl monomers and other UV crosslinking polymer systems. Thiol-ene click chemistry is used to crosslink one of the four branches of PETMP with the surface-grafted alkenyl groups.

[0006] These and other features, aspects, and advantages of the present invention will become better understood with reference to the following description and the appended claims. The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments of the invention and, together with the detailed description, serve to explain the principles of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Reference is made to the accompanying drawings, in which a complete and enabling disclosure of the invention, including the best mode thereof, for the ordinary skilled person in the art is set forth in the specification, wherein:

[0008] Figure 1 . Synthetic pathway and representative products of CNC thioesterification.

[0009] Figure 2 . FT-IR (ATR) spectra of DTDPA-grafted CNCs and optimization of the reaction using EDC or DCC coupling agents in DMF at 80 °C with extended reaction times.

[0010] Figure 3 . FT-IR spectra of acyl thiol-ene click-functionalized CNCs using different reaction conditions compared to the parent methacrylic acid esterified CNC (MA-CNC) precursor.

[0011] Figure 4 . Synthetic pathway for the thiol-ene click reaction for thiobenzoic acid (TBA)-CNC.

[0012] Figure 5 . Schematic illustration of the separation and washing procedures applicable to the TBA grafting reaction of CNCs.

[0013] Figure 6 . Solid state of freeze-dried TBA-CNC 13 C MAS NMR spectrum.

[0014] Figure 7 . TGA isotherm of freeze-dried TBA-CNC.

[0015] Figure 8 . DSC trace of freeze-dried TBA-CNC.

[0016] Figure 9 . True secant modulus (MPa) vs. percentage of tensile strain of SBR reinforced with TBA-CNC.

[0017] Figure 10 . True secant modulus TSM of rubber samples reinforced with functionalized CNC compared to carbon black CB when examined at 100%, 200%, 300% and 400% strain.

[0018] The same or similar reference numerals are used in different figures to denote the same or similar features. Detailed Description

[0019] The present invention provides a novel cellulose nanocrystal reinforcing filler for rubber compositions and methods for its preparation. For the purposes of describing the present invention, reference will now be made specifically to embodiments and / or methods of the present invention. Each example is provided as an illustration of the invention and not a limitation thereof. Indeed, those skilled in the art will appreciate that various modifications and changes can be made to the present invention without departing from the scope or essence thereof. For example, features or steps described or illustrated as part of one embodiment can be used with another embodiment or step to yield yet another embodiment or method. Accordingly, it is intended that the present invention cover such modifications and variations as fall within the scope of the appended claims and their equivalents.

[0020] Details of the results of cellulose nanocrystals CNC grafted with thiol functional groups (including thiols, thioesters and disulfides) by different synthetic methods schematically illustrated in Figure 1 are described below.

[0021] Using Steglich esterification conditions, stoichiometric 4-dimethylaminopyridine, DMAP, a catalyst, and dimethylformamide, DMF (80 °C), containing the coupling agent N,N′-dicyclohexylcarbodiimide (DCC), the disulfide 3,3′-dithiobispropionic acid (DTDPA) was grafted onto CNC. The grafting of DTDPA with a low degree of substitution SD was determined to be successful according to CHNOS elemental analysis. However, by replacing the DCC coupling agent with the more reactive 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide EDC, the DS (degree of substitution) increased threefold. DS is the average number of hydroxyl groups that have reacted on the anhydroglucose units of cellulose. Fourier transform infrared FTIR analysis confirmed the signal corresponding to the C=O stretch of the DTDPA-CNC ester at 1733 cm -1 −1 ([[]] Figure 2 )。Dispersion tests were carried out in solvents of different polarities, using the DTDPA-CNC product isolated in a paste with acetone (dispersed to 0.1 wt% in each solvent). This test showed good dispersion in ethyl acetate, toluene, and limonene, even after standing for 2 h.

[0022] When characterizing DTDPA-CNC, we can quantify the extent of single grafting of DTDPA compared to double grafting, i.e., for each grafted DTDPA group, one or two carboxylic acid ester termini are attached. First, DTDPA-CNC was reduced at room temperature using methanol / phosphate buffer (pH 8) containing dithiothreitol (DTT) in order to expose free thiol groups by cleaving the disulfide. Elemental analysis of the reduced product showed a halving of the mass percentage of sulfur (S% = 1.17) compared to DTDPA-CNC (S% = 2.29), thus indicating the presence of a significant proportion of singly grafted DTDPA (i.e., many cleaved disulfide groups result in the loss of mercaptopropionic acid groups and a corresponding loss of S%). The increase in the total grafting degree and the double / single grafting ratio was achieved through the resulting reaction optimization. By increasing the reaction time from 5 h to approximately 20 h, the total DS was increased to DS = 0.13.

[0023] The results of CNC grafted with thioester, thiobenzoic acid (TBA), via thiol-ene click chemistry are provided below. Two methods can be used for grafting. First, a stepwise method, where the first step aims for high-yield esterification (e.g., methacrylic anhydride grafting), followed by thiol-ene “click” crosslinking, as Figure 4 shown. This alkene hydrothiolation chemistry produces grafted functional groups introduced via monosulfide linkages. We essentially employed acyl thiol-ene chemistry (for small molecules), which reacts thioacids with alkenes to produce thioesters.

[0024] Olefin-grafted CNCs (e.g., methacrylic anhydride, MA-CNC) can be used as precursors for grafting thiols and thioesters via thiol-ene and acyl thiol-ene click chemistry, as Figure 4 shown in. Thioacetic acid can be used as a thioacid and reacts with MA-CNC at elevated or room temperature. Additionally, UV-initiated reactions are possible by employing the thiolactonization procedure of mercaptoalkanoic acids. The reaction mixture is typically quenched with methanol and worked up by centrifugation / washing with a solvent (e.g., methanol or acetone or a combination thereof). The reaction carried out with triethylamine base in a heated solvent, which is thought to facilitate the "Michael addition" mechanism, was most successful in converting olefins to thioester click products, achieving a DS of 0.15 in toluene, representing approximately 30% conversion. FT-IR analysis of the freeze-dried products from each of the toluene, DMF, or UV-reactions (shown in Figure 3 ) showed a small, broadened peak for the shoulder methacrylate C=O stretch measured at 1726 cm -1 −1, which was assigned to the thioester C=O expected at 1696 cm -1 −1.

[0025] To improve the compatibility of the products, thiobenzoic acid TBA was used in the click reaction to generate more hydrophobic thioester groups and thus improve the dispersibility of the functionalized CNCs in SBR. Michael addition type reactions can be carried out at 110 °C to produce products with a moderate degree of TBA group grafting, approaching a DS of 0.2. Among the solvents screened, DMF gave a product with the highest DS = 0.18, which corresponds to almost 50% conversion of the grafted alkenyl groups to acyl click products (thioester products). The click products are generally dispersible in more polar solvents, ethyl acetate and toluene, but precipitate relatively rapidly in limonene and heptane. It should be noted that the UV light-initiated reaction produced a lower DS, approximately 0.04 - 0.08, whether in DMF solvent or in pure liquid TBA at room temperature, which may be due to the inactivation of the photoinitiator during the reaction duration.

[0026] Overall optimization of the reaction conditions showed that the TBA reaction, typically carried out in excess TBA at 80 °C - 110 °C for 5 h, was insensitive to the base catalyst used, the reaction time was not long, and generally 0.1 < DS < 0.15 was obtained. Based on these results, the base catalyst can be removed, thus simplifying the procedure. The variability in S% of the TBA-CNC batches determined by CHNS elemental analysis was correlated with the faint red color of the products. For some reactions, using the same conditions (DMF with triethylamine base, 110 °C), the color of the reaction mixture could be more variable, ranging from amber to dark brown / reddish brown. This is thought to be the result of TBA decomposition, and whether this might lead to impurities in the TBA-CNC products is unknown.

[0027] Similar to the successful acyl click reactions with thioacetic acid and thiobenzoic acid, for the click grafting of methacrylated MA-CNC with commercially available branched thiols, pentaerythritol tetra(3-mercaptopropionate) or PETMP, similar reaction conditions can be carried out, such as Figure 1 as shown in. Toluene and DMF solvents can be screened with catalytic triethylamine and excess PETMP at 110 °C, and a UV light-initiated reaction can also be carried out in pure liquid PETMP at room temperature. Both the Michael addition type reaction and the UV light-initiated reaction heated in pure PETMP produce a similar DS of 0.06 - 0.07, indicating comparable reactivity of the two pathways. Each grafted PETMP molecule theoretically has 3 exposed thiol groups, and the "DS of exposed thiols" is estimated to be closer to 0.18 - 0.2. The grafting of PETMP with 4 carboxylic acid groups per molecule can be confirmed by FTIR through the strong peak at 1732 cm -1 . It is noteworthy that the reaction product in toluene is quickly dried in air to produce a free-flowing powder that can be used in rubber formulations, as it is not desirable to add the reinforcing filler as a paste in a flammable solvent to the rubber mixture. PETMP-CNC is a highly reactive system that can produce a highly rigid structure at low strain levels when compounded with rubber.

[0028] It is possible to notice the variability in the gravimetric yield determination based on mass increase, which is caused by material loss during washing / purification. Therefore, as Figure 5 shown in, a control scheme for the separation and washing procedures for the thiol grafting reaction with CNC was established. Using Figure 5 separation process 1, adding excess acetone to quench the reaction may cause complete or partial precipitation of the material. When complete precipitation occurs, the precipitate is purified with acetone as usual to obtain the product. However, when the precipitation is incomplete after quenching with acetone, the precipitate is washed with acetone while adding a co-solvent (in this case water) in a 1:1 volume ratio to the supernatant to induce precipitation. However, separation process 2, also shown in Figure 5 , is carried out by quenching the reaction with ethyl acetate. In this case, complete precipitation can be observed, and purification is restarted with acetone.

[0029] Solid state of freeze-dried TBA-CNC 13 C MAS NMR (shown in Figure 6The carbonyl carbon signal at 175 ppm was confirmed. The two carbonyl carbons (CNC ester and thioester) can overlap within this region, or the thioester signal expected at around 190 ppm can be indistinguishable from the baseline. The lack of a clear thioester peak can also indicate cleavage of the thioester during synthesis. Another small peak can be assigned to residual DMF, with a carbonyl at about 167 ppm. The signal at 128 ppm can be assigned to the aryl of the thioester, while the signal at 137 ppm can be assigned to the methacrylate olefin carbon from any ungrafted MA groups. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to analyze the thermal properties of freeze-dried TBA-CNC, and the results are shown in Figure 7 and Figure 8 . In the TGA test, the heating rate was 20 °C / min. For DSC, the temperature was first increased at a rate of 10 °C / min and then cooled at the same rate. Figure 7 The TGA curves of Figure 8 showed onset and peak decomposition temperatures at 300 °C and 323 °C, respectively. At room temperature, the material contained approximately 2.2% moisture.

[0030] Therefore, the thiol-functionalized CNC is compatible with SBR and can be directly blended with the rubber components. The thiol-functionalized CNC is used as a renewable and sustainable reinforcing agent in rubber, which can replace non-renewable materials such as carbon black. Table 1 provides two example formulations for rubber blending. The rubber properties can be adjusted by regulating the dosage of specific components in the blend, such as ZnO and / or crosslinking agents. The mixing of rubber with the thiol-functionalized CNC can be carried out using conventional rubber processing equipment (such as an internal mixer), and the material can be added as a dry powder or mixed as a paste with a solvent-solid content of about 7%-40%. Conventional rubber processing equipment and procedures can be used, such as a Haake mixer equipped with a pair of Banbury rollers. In the first step, the elastomer can be mixed with the olefin-functionalized CNC, ZnO, stearic acid, SAD, and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine 6PPD at specific temperatures and speeds (such as 90°C - 120°C and 70 rpm - 100 rpm, respectively). Then, S and N,N-dicyclohexyl-2-benzothiazolesulfenamide CBS can be mixed at a lower temperature (such as 50°C and 30 rpm). The compounded rubber can be vulcanized in a steel mold using a hydraulic press at a high temperature (such as 150°C). If the functionalized CNC is used as a paste, the mixing and solvent evaporation can be carried out in one of two methods. Method 1: Mix the paste with the elastomer in a Haake mixer and evaporate it, for example, at a temperature above the boiling point of the solvent. Method 2: Dissolve the elastomer in a solvent miscible with the paste and mix them well.

[0031] Table 1. Example of a rubber compounding formulation. (*Equivalent of 27 phr of grafted CNC + 8.1 phr of TBA, which is the same volume percentage as N234 carbon black.)

[0032]

[0033] The final product can be dried using air drying, vacuum drying, freeze drying, spray drying, or any other suitable technique that allows the direct removal of the solvent from the system. Subsequently, this dry material can be mixed with the rubber components and vulcanized. It is also possible to use a solvent paste containing the functionalized CNC and directly blend it with the rubber components while drying the solvent. The rubber reinforced with the thiol-functionalized CNC exhibits a strain behavior of about 350%-450% and a true secant modulus approaching 20 MPa at maximum strain. This material is also characterized by a high true secant modulus at low strain values. For example, for the vacuum-dried TBA-CNC, the true secant modulus is about 9 MPa at 100%, about 11 MPa at 200%, and about 15 MPa at 300%. Figure 9 and Figure 10Describes the basis for the excellent reinforcement of thiol-functionalized CNCs in rubber when compared to carbon black, a non-renewable material commonly used for rubber reinforcement. Figure 9 Shows the true secant modulus curves of five vacuum-dried samples (replicates). The figure clearly illustrates the excellent hardening and reinforcement at strains < 150%, which is attributed to the good connectivity of the thiol-functionalized CNC nanoparticles and the development of an interpenetrating network. When the material is stretched to 300%, the true secant modulus (TSM) remains high, achieving > 14 MPa, which is more than twice the TSM of rubber reinforced with CB, as Figure 10 shown in. This indicates excellent dispersion and interfacial properties between the thiol-functionalized CNC and SBR, as well as the effectiveness of the former in generating an effective interpenetrating network for reinforcement and in achieving good crosslinking through thiolation between the elastomer and the thiol-functionalized CNC. Figure 9 and Figure 10 also indicates that if the thiol-grafted CNC is applied as a paste and then dried, or vacuum-dried from a solvent elastomer mixture form, the results and thus the reinforcement potential are improved.

[0034] Selected combinations of aspects of the disclosed technology correspond to various different embodiments of the invention. It should be noted that each of the exemplary embodiments presented and discussed herein should not be construed as limiting the subject matter. Features or steps described or depicted as part of one embodiment may be used in combination with aspects of another embodiment to yield yet additional embodiments. Additionally, certain features may be interchanged with similar devices or features not explicitly mentioned that perform the same or similar functions.

[0035] The terms "a", "an", and the singular form of a word shall be considered to include the plural form of the same word, such that these terms mean providing one or more of something. The terms "at least one" and "one or more" are used interchangeably. A range described as "between a and b" includes the values of "a" and "b". The citation of any document does not admit that the document is prior art with respect to any invention disclosed or claimed herein, nor does it admit that the document alone or in combination with any other one or more reference documents teaches, suggests, or discloses any such invention. Additionally, in the event of any conflict between the meaning or definition of a term in this document and the meaning or definition of the same term in a document incorporated by reference, the meaning or definition given to the term in this document shall prevail.

Claims

1. A method for preparing a functionalized cellulose nanocrystal filler having an ester functional group containing mercaptan sulfur for a rubber composition, comprising: Acid-esterifying and hydroxylating cellulose nanocrystals with acids selected from the group consisting of 3-mercaptopropionic acid, 3-(acetylthio)propionic acid, and dithiodipropionic acid to produce esterified cellulose nanocrystals; Reacting the esterified cellulose nanocrystals with a thioester by thiol-ene click chemistry.

2. The functionalized cellulose nanocrystal filler according to claim 1, wherein the esterification is carried out by grafting with methacrylic anhydride.

3. The method for preparing a functionalized cellulose nanocrystal filler having an ester functional group containing mercaptan sulfur according to claim 1, further comprising: Quenching the reaction with acetone.

4. The method for preparing a functionalized cellulose nanocrystal filler having an ester functional group containing mercaptan sulfur according to claim 1, further comprising: Quenching the reaction with ethyl acetate.

5. The method according to claim 3 or claim 4, further comprising: Washing the precipitate with acetone.

6. The method according to claim 3, further comprising: Separating the precipitate from the supernatant; Washing the precipitate with acetone; Adding a co-solvent to the supernatant to induce precipitation, thereby producing a second precipitate; and Washing the second precipitate with acetone.

7. The method according to any one of the preceding claims, further comprising: Drying the final product to produce a dried functionalized cellulose nanocrystal filler.

8. The functionalized cellulose nanocrystal filler according to claim 7, wherein the filler is dried by any technique belonging to the technical group consisting of air drying, vacuum drying, freeze drying, spray drying, and combinations thereof.

9. The method according to claim 1, wherein the mercaptan is grafted onto the cellulose nanocrystals by esterification with hydrochloric acid, whereby the surface is uncharged.

10. A method for preparing a functionalized cellulose nanocrystal filler having an ester functional group containing mercaptan sulfur for a rubber composition, comprising: Esterifying hydroxylating cellulose nanocrystals with hydrochloric acid; Reacting the esterified cellulose nanocrystals with a thioester by thiol-ene click chemistry.

11. The method according to claim 10, further comprising: Increasing the density of carboxylate groups to impart charge to the functionalized cellulose nanocrystals.

12. A rubber composition comprising a filler produced according to any one of the preceding claims.